STUDI KASUS TRANSFER PRICING PADA PERUSAHAAN MULTINASIONAL DI SEKTOR TEKNOLOGI - Ade Yulita Sihombing; Prasasti Ardella; Quddusi Shara Ayuni; Yuli Natalia Simbolon; Lusita Debora Marpaung; Tia Novira Sucipto (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This study analyzes transfer pricing practices in multinational technology companies, focusing on the complexities of global financial management and tax compliance. Transfer pricing, which involves setting prices for the transfer of technology, finished goods, or services between company entities in different jurisdictions, significantly impacts a company's financial structure and tax obligations. The study highlights the importance of fair internal pricing to avoid illegal tax avoidance practices and emphasizes the necessity of compliance with OECD guidelines. Risk management in transfer pricing is identified as crucial due to the potential legal and reputational risks associated with tax audits by local authorities. Additionally, operational efficiency in transfer pricing strategies can help companies optimize resource allocation and make more informed investment decisions. The study concludes that effective transfer pricing management requires a holistic and coordinated approach, considering fair pricing, tax compliance, risk management, operational efficiency to mitigate legal and tax risks while maximizing shareholder value globally.